Sarcopenia and low muscle radiodensity associate with impaired FEV1 in allogeneic haematopoietic stem cell transplant recipients. Issue 6 (29th July 2020) - Mishra, Asmita; Bigam, Kevin D.; Extermann, Martine; Faramand, Rawan; Thomas, Kerry; Pidala, Joseph A.; Baracos, Vickie E.
Abstract: Background: Quantification of skeletal muscle using computed tomography (CT) is accessible using cancer patients' standard oncologic images. Reduced muscle mass may be related to reduced respiratory muscle strength; however, the impact of this on lung functional parameters is not characterized in adult allogeneic haematopoietic stem cell transplant (alloHCT) recipients. Methods: A consecutive retrospective series ( n = 296) of patients who had alloHCT at a comprehensive cancer centre between March 2005 and April 2015 were included. Pre‐transplant CT scans were used to quantify skeletal muscle and adipose tissue at the fourth thoracic (T4) and/or third lumbar (L3) level. Tumour and patient characteristics were recorded, including forced expiratory volume in 1 second (FEV1 ) by spirometry. Regression models were created to characterize predictive relationships. Results: A total of 296 patients (♂ n = 161; ♀ n = 135) were included, all of whom had chest CT as part of standard care; a subset of these ( n = 215, 72.6%) also had abdominal CT. Diagnoses were non‐Hodgkins lymphoma ( n = 165), acute myeloid leukaemia ( n = 66), Hodgkin's disease ( n = 14), acute lymphocytic leukaemia ( n = 14), myelodysplastic syndromes ( n = 18), and other ( n = 19). In multivariable linear regression adjusted for sex ( P < 0.0001), age ( P < 0.0001), haematopoietic cell transplantation‐specific co‐morbidity index ( P = 0.010), and parameters of pulmonary function testing (defined by spirometry, P < 0.0001), both T4 muscle index [ β 0.127 (95% confidence interval 0.019; 0.252), P < 0.0001] and T4 muscle radiodensity [ β 0.132 (95% confidence interval 0.087; 0.505), P = 0.006] were independently associated with FEV1 ; disease risk index ( P = 0.877) and Karnofsky performance status ( P = 0.548) were not associated with FEV1 . Similar conclusions were obtained when L3 muscle index and radiodensity were considered. Unlike T4, L3 muscle index values can be compared with published cut‐off values for sarcopenia. Overall rates of sarcopenia were uniformly higher in the HCT population than in age‐matched and sex‐matched patients with solid tumours [alloHCT ♂64.7% vs. solid tumour ♂56.6% ( P < 0.001); alloHCT ♀57.6% vs. solid tumour ♀36.0% ( P < 0.001)]. Significant but moderate correlations ( P < 0.001) were found for muscle area and radiodensity between L3 and T4, for both men and women; adipose tissue quantity also correlated significantly ( P < 0.001) between L3 and T4 for both men and women. Conclusions: Lumbar or thoracic CT images are useful for body composition assessment in this population and reveal high rates of sarcopenia, similar to those reported in very elderly patients. Reduced muscle mass and radiodensity associate with impaired FEV1 even after adjustment for clinical covariables including co‐morbidities, performance status, disease risk, and mild intrinsic pulmonary disease (chronic obstructive pulmonary disease) defined by spirometry.